From corporations to commissioners : municipal government and urban change in Leinster, 1835-65 - Hester, Patrick J. (Trinity College (Dublin, Ireland). Department of Geography, 2009)
Following an 1835 report, a process of reform of Irish town government took place. This thesis examines the process and the major shift which occurred in the government of market towns in Leinster between 1835 and 1865. It also examines the parallel increase in the interest of central government in Irish urban administration. As a consequence of the Act of Union, the corporations responsible for the administration of these towns, made up of sectarian, often absentee, protestant elites, became almost totally moribund. Neglect and corruption became the rule. These corporations were allowed to continue in existence for many decades without any vestige of state control or accountability. Their members were usually made up of the families and agents of the local landlord who acted as patron of the town and appointed either himself or his agent as its ‘sovereign’ or ‘burgomaster’.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin